OPTIMIZATION OF PECTIN YIELD FROM KEPOK BANANA PEEL (Musa Balbisiana BBB) USING ULTRASONIC EXTRACTION WITH ACETIC ACID AND SULFURIC ACID SOLVENTS - Silvia, Putri Zulva; Saputri, Desi Riana; Damayanti, Damayanti; Auriyani, Wika Atro; Fahni, Yunita; Sanjaya, Andri; Yusupandi, Fauzi; Yuniarti, Reni; Safitra, Edwin Rizki; Tiara, Mega; Pajrin, Alfina; Alhanif, Misbahudin (JURNAL INTEGRASI PROSES, 2025)
In Indonesia, banana fruit production occupies the first position compared to other fruits. The peel constitutes approximately 40% of the total weight of the fruit, thus producing a large amount of waste. The white part of the banana peel (mesocarp) has the potential to serve as a source of pectin, which primarily functions as a thickening and gel-forming agent. Pectin can be extracted from fruit peel using acidic solvents. This research was performed using the ultrasound-assisted extraction (UAE) method. This study utilized banana peel waste produced by banana chips traders in the city of Bandar Lampung and aims to determine the effect of temperature, time, and type of extraction solvent on the yield of pectin extract from kepok banana peels (Musa balbisiana BBB), and to identify the molecular functional groups of extracted pectin with the highest yield. Based on this research, it is known that the yield increases with increasing temperature and extraction time. The optimum condition for pectin extraction from kepok banana peel (Musa balbisiana BBB) was obtained at a temperature of 70 °C with a time of 90 minutes for both acetic acid and sulfuric acid solvents, yielding 12.63 and 14.09%, respectively. FTIR spectroscopy analysis reveals that the pectin extract exhibits functional groups with characteristic absorption bands in the specific wavelength regions consistent with pectin’s structure. These include O–H stretching vibrations, –CH₃ groups in the methoxyl (COOCH₃) branch, C–H bonds, C=O carbonyl groups, C–O bonds, and ether (C–O–C) linkages.